2016
DOI: 10.1016/j.forsciint.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder associates with violent criminality in women: A population based follow-up study of adolescent psychiatric inpatients in Northern Finland

Abstract: Various psychiatric problems in adolescence and early adulthood have been shown to associate with criminal behaviour. In this study the association of personality disorders (PDs) with criminal behaviour was examined in adolescents treated in psychiatric hospitals. The study sample consisted of 508 adolescents (age 13-17) admitted to acute psychiatric impatient care between April 2001 and March 2006. Crime data was obtained from the Finnish Legal Register Centre on September 2013. The Schedule for Affective Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…These results are partly consistent with Tschoeke et al's (2014) study that reported less severe delusions, conceptual disorganization and negative symptoms in adult patients with BPD, compared with patients with SZ. The higher hostility scores in the current youth BPD sample are consistent with inappropriate and intense anger being a core feature of this disorder that declines with age (Zanarini et al, 2007), as well as with evidence indicating that, in young people, BPD is a risk factor for perpetrating violence (Arola et al, 2016;González, Igoumenou, Kallis, & Coid, 2016).…”
Section: Discussionsupporting
confidence: 78%
“…These results are partly consistent with Tschoeke et al's (2014) study that reported less severe delusions, conceptual disorganization and negative symptoms in adult patients with BPD, compared with patients with SZ. The higher hostility scores in the current youth BPD sample are consistent with inappropriate and intense anger being a core feature of this disorder that declines with age (Zanarini et al, 2007), as well as with evidence indicating that, in young people, BPD is a risk factor for perpetrating violence (Arola et al, 2016;González, Igoumenou, Kallis, & Coid, 2016).…”
Section: Discussionsupporting
confidence: 78%
“…Regarding non-psychotic disorders, research has revealed that between about half and two thirds of young offenders meet the diagnostic criteria for a conduct disorder, and between about a third and a half for a substance-use disorder [36,37]. Moreover, both antisocial [38] and borderline [39,40] personality disorders associate with criminality. Our delinquent sample considerably resembled these above-mentioned descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Danie Martin de Barros and Antonio de Pádua Serafim, stated that personality disorders of antisocial and borderline are highly predicted to make violence [3]. Research conducted by Riikka Arola et al, found that borderline personality disorder is a factor of violence attacks by women [4].…”
Section: Introductionmentioning
confidence: 99%